SHALLOT VARIETIES DEVELOPED FOR THE CONDITIONS OF THE SOUTH OF WEST SIBERIA - S. V. Zharkova; O. V. Malykhina; Ye. V. Shishkina (Овощи России, 2018)
Shallot is one of the most popular onion crops at present. This is a multi-purpose crop in terms of possible use of its economically valuable features. In order to realize the potential of this crop, its varieties are needed. The work on the development of varieties adapted to the conditions of the south of West Siberia was carried out by the plant breeders of the West Siberian Vegetable Experimental Station from 1999 through 2018. The research goal was to study introduced and local forms of shallot variety accessions and to obtain varieties adapted to the conditions of Siberia with high indices of economically valuable features. In 1999, the plant breeders began working with the collection of shallot hybrid material obtained by polycross method at the Siberian Research Institute of Crop Production and Plant Breeding. Shallot variety accessions introduced in different climatic zones (Far East, Kazakhstan, Krasnodar, the Urals, Siberia, Non-Chernozem Zone and Holland) were used as initial forms for hybridization. Five variety accessions were obtained; they successfully underwent the State Variety Testing and were released.